“We shall know a place by its names”: Co-existing place names in Bindura, Zimbabwe - Dorcas Zuvalinyenga (EchoGéo)
This article examines the layered co-existence and simultaneous use of a complex range of toponyms in the town of Bindura in Zimbabwe. It proposes that the concurrent use of different names for the same place indicates the ongoing negotiation, contestation and articulation of diverse identities in Bindura on the basis of history, age, class, race, gender, ideology, language, culture, communication, and power. The implications of plural toponymies on members of the selected community and their relationship to a place are explored in as far as the toponymies and toponymic inscriptions may be said to reveal the operation of various discourses, identities and social representations that are traced from precolonial times to the present. The article follows Tucci, Ronza and Giordano’s study of what they call the “layering (of) the toponymic tapestry” whereby toponyms can be a reflection of a place’s long and contested social and political history. Fragments of different toponymic regimes and hegemonic discourses that took over one after the other over time remain inscribed in these place names, thus originating “a complex tapestry” in which different pasts, histories and present day experiences revive and conflicting ideologies and identities co-exist. In essence, names and naming practices of a place gives us windows into the events or behaviours of a particular place and its inhabitants.